Gender violence and shame. The visible and the invisible, from the clinical to the social systems - Margherita, Giorgia; Troisi, Gina (La camera blu. Rivista di studi di genere, 2014)
The traumatic experience of violence is, in its nature, unspeakable. It causes in the victim a deep wound in identity, changes in the dynamics of psychic investments producing a failure of the ability to symbolize, thus breaking the rules that characterize the usual development of thought. Some affections related to the body prevail, above all the shame which expresses itself in characteristics which reinforce the element of trauma. The loss of a capacity to represent and symbolize is not only a psychic dynamic, but it also reproduces itself in the social systems, shaping that zone of “silent concealment”, that drives the phenomenon of gender violence. The psychoanalytical reflection on the relationship between guilt and shame seems to be a priority in dealing with and at the same time highlighting the risk of victim blaming intended in terms of the unconscious defensive dynamics expressed by the social systems. We will consider the importance in the therapeutic intervention of the work of reconstruction and historicization, to be able to reactivate representation which allows the integration and the chance to distinguish the imaginary plane of the traumatic event from the real one. The psychoanalytical approach to the groups provides an interpretative model to articulate the psychic and the social space.